DNA Delivery from Matrix Metalloproteinase Degradable Poly(ethylene glycol) Hydrogels to Mouse Cloned Mesenchymal Stem Cells - Lei, Yuguo (2008)
The ability to genetically modify mesenchymal stem cells (MSCs) seeded inside synthetic hydrogel scaffolds would offer an alternative approach to guide MSC differentiation and to study molecular pathways in three dimensions than protein delivery. In this report, we explored gene transfer to infiltrating MSCs into matrix metalloproteinase (MMP) degradable hydrogels that were loaded with DNA/poly(ethylene imine) (PEI) polyplexes. DNA/PEI polyplexes were encapsulated inside poly(ethylene glycol) (PEG) hydrogels crosslinked with MMP degradable peptides via Michael Addition chemistry. A large fraction of encapsulated polyplexes remained active after encapsulation (65%) and the mechanical properties of the hydrogels were unchanged by the encapsulation of the polyplexes. Cells were seeded inside the hydrogel scaffolds using two different approaches, clustered and homogeneous. The viability of MSCs was similar in hydrogels with and without polyplexes. Transgene expression was characterized with time using a secreted reporter gene and showed different profiles for clustered and homogeneously seeded cells. Clustered cells resulted in cumulative transgene expression that increased through the 21-day incubation, while homogeneously seeded cells resulted in cumulative transgene expression that plateaued after 7-days of culture. The use of hydrogel scaffolds that allow cellular infiltration to deliver DNA may result in long lasting signals in vivo, which are essential for the regeneration of functional tissues.